Pengembangan Game Edukatif Berbasis Nilai Islami untuk Meningkatkan Berpikir Kritis Peserta Didik Madrasah Ibtidaiyah (MI) - Sopyan, Arisal (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
This study focuses on developing an Islamic-values-based educational game to enhance critical thinking skills among students at Madrasah Ibtidaiyah (MI). In the digital era, MIs face challenges in adapting technology for learning, including limited infrastructure, teacher competency, and curriculum relevance. A significant issue is the low critical thinking skills in some subjects, as traditional learning models often fail to foster higher-order thinking abilities like analysis, evaluation, and problem-solving. Critical thinking is essential for 21st-century challenges and the demands of the Industrial Revolution 4.0. Educational games offer a creative and interactive learning alternative, proven to boost learning motivation, active participation, and critical thinking through engaging experiences. They also foster cooperation, problem-solving and provide immediate feedback. A key challenge is integrating Islamic values into digital learning media, which not only builds student character but also aligns educational innovation with Islamic education goals. This research aims to develop an educational game that effectively enhances critical thinking while internalizing Islamic values such as honesty, responsibility, and cooperation, ensuring comprehensive and meaningful learning.